Spinodal dewetting in liquid crystal and liquid metal films - Mecke, Klaus; et al. (Science, 1998)
Theory predicts that dewetting of a homogeneous liquid film from a solid surface may proceed via unstable surface waves on the Liquid. This phenomenon, usually termed spinodal dewetting, has been sought after in many systems. Observations in liquid crystal and Liquid metal films showed that, as expected, the emerging structures were similar to those found for spinodal decomposition in mixtures. Certain differences, however, could be attributed to peculiarities of the wetting forces in these two dissimilar systems, thereby demonstrating the role of nonlinearities inherent in the wetting forces.